2020
DOI: 10.3390/w12040990
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bottom Ash as Filter Media for Construction Site Runoff Control

Abstract: The potential application of bottom ash (BA) for construction site runoff control as an alternative filter media with high removal efficiency of total suspended solids (TSS) and longer operation period were evaluated. Both lab-scale single-layer and pilot-scale multi-layer filtration experiments were performed using BA filter media with different particle sizes and various volumetric flow rates. Due to the mesoporous, irregular, and spherical shape of gravel-size BA filter media used in this study, relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The sedimentation effect of the sedimentation tank can be simulated by numerical simulation; in addition, the appropriate application relationship between sedimentation tank volume and CSM property can be established through the accumulation of empirical data. Filter media [64] and a flocculating agent [65,66] have also been studied for settling sediment in drainage. The sedimentation tank can achieve a higher sediment interception effect by combining with these methods.…”
Section: Analysis Of the Weight Of Influencing Factorsmentioning
confidence: 99%
“…The sedimentation effect of the sedimentation tank can be simulated by numerical simulation; in addition, the appropriate application relationship between sedimentation tank volume and CSM property can be established through the accumulation of empirical data. Filter media [64] and a flocculating agent [65,66] have also been studied for settling sediment in drainage. The sedimentation tank can achieve a higher sediment interception effect by combining with these methods.…”
Section: Analysis Of the Weight Of Influencing Factorsmentioning
confidence: 99%
“…The service life of the media may be prejudiced by other components presents in the stormwater, which can control and influence the result of the modeling. Joo et al [50], Conley et al [51] and Kandra et al [52] reported clogging of filter media due to the concentration of suspended solids in the stormwater. The clogging phenomena have been also simulated in infiltration systems treating rainfall-runoff [53].…”
Section: Profile Of Zn Concentration and Percentage Removalmentioning
confidence: 99%